1996
DOI: 10.1097/00003072-199610000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Imaging Results Using In-111 Labeled CYT-356 (Prostascintst) in the Detection of Recurrent Prostate Cancer

Abstract: To evaluate whether In-111 capromab pendetide (an antibody conjugate directed to a glycoprotein found primarily on the cell membrane of prostate tissue) radioimmunoscintigraphy can localize residual or metastatic prostatic carcinoma in 15 patients after prostatectomy and lymphadenectomy for prostatic carcinoma with rising serum prostate-specific antigen. One patient with 0.6 ng/ml serum prostate-specific antigen had normal imaging results and 14 patients had scintigraphic evidence of residual prostatic bed or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Prior investigations have demonstrated that 111 In-capromab pendetide immunoscintigraphy is safe, with mild adverse effects and minimally elevated human antimouse antibody levels on rare occasion. 18,19 PSMA is a 100-kD transmembrane glycoprotein produced by both benign and malignant prostate epithelial cells. PSMA is expressed more abundantly in malignant prostate tissue compared with normal or hypertrophic prostate tissue and in poorly differentiated tumors compared with well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have demonstrated that 111 In-capromab pendetide immunoscintigraphy is safe, with mild adverse effects and minimally elevated human antimouse antibody levels on rare occasion. 18,19 PSMA is a 100-kD transmembrane glycoprotein produced by both benign and malignant prostate epithelial cells. PSMA is expressed more abundantly in malignant prostate tissue compared with normal or hypertrophic prostate tissue and in poorly differentiated tumors compared with well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It also affects neighboring cells with a heterogeneous antigen expression or insufficient vascularization, which is so called "bystander effect" (Rzeszowska-Wolny et al, 2009). An initial immunoscintigraphic approach targeting PSMA was done with the 111 Indium ( 111 In) labeled anti-PSMA monoclonal antibody 7E11 (Capromab Pendetide (Prosta Scint®), Cytogen, Philadelphia, PA) (Kahn et al, 1994;Sodee et al, 1996;Kahn et al, 1998). With this radioimmunoconjugate a higher sensitivity was reached in the imaging of prostate cancer soft tissue metastases compared to Computed Tomography (CT) or Magnetic Resonance Tomography (MRT) .…”
Section: Anti-psma Radioimmunotherapymentioning
confidence: 99%
“…Figure 3 shows patients free of biological recurrence, with PSA greater than 0.3 and 1.0 ng/ml. Four patients developed a PSA 44.0 ng/ ml, one had a negative biopsy, bone scan, pelvis MRI, Prostacinct study 19 (In-111 labeled Copramab Pendetide, Cytogen Corp., Princeton, NJ, USA) and has had no other treatment. Three patients began hormone treatment on the basis of a rapidly rising PSA: one had two sets of TRUS-guided biopsies that were negative for any cancer or viable residual prostate tissue.…”
Section: Participant Characteristicsmentioning
confidence: 99%